The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.neuron.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptors—Noxious Stimulus Detectors

Abstract: In order to deal effectively with danger, it is imperative to know about it. This is what nociceptors do--these primary sensory neurons are specialized to detect intense stimuli and represent, therefore, the first line of defense against any potentially threatening or damaging environmental inputs. By sensing noxious stimuli and contributing to the necessary reactions to avoid them--rapid withdrawal and the experience of an intensely unpleasant or painful sensation, nociceptors are essential for the maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
704
2
27

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 828 publications
(735 citation statements)
references
References 119 publications
(155 reference statements)
2
704
2
27
Order By: Relevance
“…This sensitization, described as increased efficiency of synaptic conduction, is evident in every patient with chronic pain due to changes in the central, as well as the peripheral nervous system [24]. Several chemical irritants, such as cytokines, matrix metalloprotease, fibroblast growth factor, leukotrienes, thromboxanes, prostaglandins, immunoglobulins, among others, known to cause inflammation, are considered to play a role in nociceptor sensitization [37].…”
Section: Discussionmentioning
confidence: 99%
“…This sensitization, described as increased efficiency of synaptic conduction, is evident in every patient with chronic pain due to changes in the central, as well as the peripheral nervous system [24]. Several chemical irritants, such as cytokines, matrix metalloprotease, fibroblast growth factor, leukotrienes, thromboxanes, prostaglandins, immunoglobulins, among others, known to cause inflammation, are considered to play a role in nociceptor sensitization [37].…”
Section: Discussionmentioning
confidence: 99%
“…We found here that low dose capsaicin, which evokes a near-pure thermal hyperalgesia without C-fiber destruction (27,33), produced much reduced pain perception in the AQP1 Ϫ/Ϫ mice. Remarkable phenotype differences were also found upon challenge with bradykinin and PGE 2 , which are major components of the inflammatory soup and sensitize small DRG neurons through G protein-coupled receptors targeting TTX-R and TRP channels (43). Regarding PGE 2 testing, Shields et al (15) reported no differences for a hypoosmotic challenge in the setting of PGE 2 -induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…95), the suppressive influence of innocuous A-fiber mechanosensitive inputs at a systems level (18), and the extrapolation of cellular assays to nociception (e.g., poking, ref. This topic is reviewed in more detail elsewhere (12,19,(91)(92)(93).…”
Section: Transduction Of Noxious Mechanical Stimulimentioning
confidence: 99%